A new approach for the vitrification of municipal solid waste incinerator bottom ash by microwave irradiation. (15th February 2021) - Flesoura, Georgia; Dilissen, Nicole; Dimitrakis, Georgios; Vleugels, Jef; Pontikes, Yiannis
Abstract: Encouraging the transition to a circular economy, the valorization of municipal solid waste incinerator (MSWI) bottom ash (BA) has received considerable attention in many processes. In the present work, flash microwave vitrification was effectively realized in a single mode cavity operating at 2.45 GHz within 1.5 min. The closed-loop process was evaluated in terms of energy and power input, treatment time and vitrified bottom ash (VBA) yield rate. The required minimum energy consumption was ∼3300 kJ/kg. By conducting thermo-electromagnetic multiphysics simulations, the heating mechanism of BA by microwave irradiation was underpinned. This relied on the generation of microwave-induced hot spots inside the material and high power density, in the order of 3 × 10 7  W/m 3, that triggered the onset of BA melting at high heating rates. The inherent cold environment of the microwave cavity, due to the absence of any insulation material, in conjunction with the high silica content of BA promoted the glass forming ability of the melt. This allowed a natural fast cooling of the melt and VBA production, avoiding the cost and environmental impact accompanying conventional quenching. Preliminary characterization of the highly amorphous VBA product was performed and its exothermal heat flow after alkali activation revealed the potential incorporation in the binder of novel building materials. Graphical abstract: Image 1 Highlights: Realization of flash microwave vitrification of BA with 3300 kJ/kg energy input. Energy density driven heating mechanism of BA favored by high power input and short processing time. Microplasmas prompting BA melting at high heating rates. Promising use of VBA as a precursor for alkali-activated materials.